Interactive Digital Comic Learning Media Based on Literacy in Social Studies Content for Elementary School Students - Wijayanti, Ni Made Nur Adi; Wulandari, I Gusti Agung Ayu; Sutyaningsih, Anak Agung Ayu Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This research was motivated by the low interest and understanding of students in the topic Exploring Countries and ASEAN Cooperation in sixth-grade Social Studies, which is due to the limited availability of engaging and interactive learning media. The aim of this study was to develop and analyze a literacy-based interactive digital comic as a learning medium, and to examine its feasibility, students' responses, and its effectiveness. The development model used was the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 23 sixth-grade students. Data collection methods included observation, interviews, questionnaires, and tests. The instruments used were questionnaire sheets and multiple-choice tests. Data analysis techniques were conducted using both descriptive qualitative and quantitative approaches. The results showed that the value of t obtained was greater than the t table (2.839 > 0.914), indicating that the literacy-based digital comic on exploring countries and ASEAN cooperation is effective in helping students achieve scores above the Minimum Mastery Criteria (KKTP). The media was also effective in improving students’ understanding of the Social Studies material. The implication of this research is that literacy-based interactive digital comics can serve as an innovative alternative medium to support meaningful and enjoyable Social Studies learning.